The right to landscape : contesting landscape and human rights - 535200 Egoz, Shelley; Makhzoumi, Jala, 1949-; Pungetti, Gloria (Farnham, Surrey, England ; Burlington, VT : Ashgate Pub. Company)
Includes bibliographical references and index